Semi‐idealized simulations of wintertime flows and pollutant transport in an Alpine valley. Part II: Passive tracer tracking. (28th January 2020) - Sabatier, Tiphaine; Largeron, Yann; Paci, Alexandre; Lac, Christine; Rodier, Quentin; Canut, Guylaine; Masson, Valéry
Abstract: Under wintertime quiescent conditions, thermally driven circulations represent one of the only sources of tracer dispersion over mountainous terrain. Those circulations can be unequally developed at a valley scale since they strongly depend on local morphological arrangement. At the same time, very heterogeneous pollutant distribution can be observed, as for instance in a French Alpine basin located in the Arve River valley. This complex basin regularly shows large variations in pollutant concentrations with certain sectors suffering from poor wintertime air quality. On the other hand, the surrounding tributary valleys appear to be less affected, suggesting that the basin local dynamics may participate in pollutant trapping. The present study intends to classify the pollutant transport mechanisms in terms of efficiency and to identify the most dynamically vulnerable atmospheric volumes regarding pollutant accumulation. This is achieved through a set of semi‐idealized high‐resolution numerical simulations reproducing a full diurnal cycle with passive tracers released continuously at a constant rate. The model is used as a laboratory in order to quantify the influence of several processes on transport mechanism efficiency. This approach underlines the high efficiency of vertical transport by anabatic winds while horizontal transport efficiency by up‐valley wind systems remains weak, leaving the surrounding tributary valleys almost unaffected by the basin pollution during daytime. At night, the efficiency of horizontal transport by the down‐valley wind systems depends on the tracer source location within the basin. In addition, the tracers emitted within the tributary valleys do not reach the basin bottom because of thermal stratification and local morphological arrangement but rather degrade the air quality of mid‐altitude villages lying along the basin sidewalls. Abstract : The transport of pollutants in an Alpine valley strongly depends on the local orography surrounding the emission sources. This local dependence may lead to very heterogeneous pollutant distribution over restricted areas, as is currently observed within a semi‐enclosed basin located in the French Alps. A passive tracer tracking is performed from high‐resolution mesoscale simulations in order to identify the most effective transport mechanisms and the most dynamically vulnerable atmospheric volumes regarding pollutant accumulation.